2023
DOI: 10.1108/ejtd-07-2022-0083
|View full text |Cite
|
Sign up to set email alerts
|

The role of mentors’ paradox mindset on career mentoring: application of attachment theory

Abstract: Purpose This study aims to investigate the relationship between mentors’ paradox mindset and career mentoring directly and indirectly through self-efficacy and work engagement, drawing insights from attachment theory. Design/methodology/approach A serial mediation model was tested using survey data from 297 employees working in a bank company in China. Findings Paradox mindset had a significant indirect effect on career mentoring through self-efficacy and work engagement, self-efficacy had a significant in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
(129 reference statements)
1
0
0
Order By: Relevance
“…We also found that mentorship that addressed diversity and fostered independence was significantly associated with self-efficacy in career advancement among post-doctoral fellows and early-career faculty from underrepresented groups. These are consistent with previous findings that show that mentor mindset (e.g., addressing diversity, understanding, and facilitating identity work) has a significant effect on the self-efficacy and work engagement of mentees [21].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that mentorship that addressed diversity and fostered independence was significantly associated with self-efficacy in career advancement among post-doctoral fellows and early-career faculty from underrepresented groups. These are consistent with previous findings that show that mentor mindset (e.g., addressing diversity, understanding, and facilitating identity work) has a significant effect on the self-efficacy and work engagement of mentees [21].…”
Section: Discussionsupporting
confidence: 93%